FEASIBILITY AND SENSITIVITY STUDY OF FARMING SYSTEM TO INCREASE ACCESSIBILITY OF SMALL COFFEE FARMERS TO THE FINANCIAL INSTITUTIONS - Ati Kusmiati (UPT Penerbitan Universitas Jember, 2012)
The objectives of this study were: (1) to analyze financial feasibility and sensitivity of small coffee farming; (2) to identify the role and the relationship between financial institutions and small coffee farmers. The analytical methods were NPV, net B/C, IRR, payback period, sensitivity, and Venn diagram. The results of this study showed that coffee farming system in the Sidomulyo village and Pace village were financially feasible and were not sensitive to the changes of costs and selling prices. Financial institution that had close relationship and important role in Pace Village was trader collectors. Meanwhile in the Sidomulyo Village were trader collectors and Cooperative of Buah Ketakasi. The right financial model of small coffee farmers established a network of financial cooperation with the principle of